Thrombin activatable fibrinolysis inhibitor antigen and activity levels in normal pregnancy. (16th November 2010) - Huq, FY; Chi, C; Riddell, A; Whitlow, B; Kadir, RA
Abstract : Background: Thrombin activatable fibrinolysis (TAFI) is a glycoprotein that inhibits fibrinolysis. Pro-TAFI is cleaved by Factor IIa – Thrombomodulin complex, producing actived TAFI (TAFI:Ac). Pregnancy is a hypercoaguable state associated with increased levels of pro-coagulant factors; enhanced thrombin generation and impaired fibrinolysis. TAFI may contribute to the decreased fibrinolysis seen in pregnancy. Currently there are conflicting reports on TAFI antigen (TAFI:Ag) levels in pregnancy and no data on the dynamic changes in levels and activity during pregnancy and its correlation with adverse pregnancy outcome. Method: Consecutive TAFI:Ag and activity (TAFI:Ac) levels were measured during the first, second and third trimester in 80 women. All participants in the study had no co-morbidities and had an uncomplicated singleton pregnancy. Results: TAFI:Ag levels significantly increased with gestation peaking in the third trimester with mean levels of 120, 139 and 148 μg/ml in the first, second and third trimesters respectively (p<0.035). TAFI:Ac levels significantly increased between the first and second trimesters with mean values of 47 and 52 μg/ml respectively (p<0.01). TAFI:Ac levels then plateaued in the third trimester (with a mean value of 53 μg/ml). Conclusion: TAFI antigen and activity levels are increased in normal pregnancy